CHEMISTRY AT WORK AT THE MAMALA RIVER - A. ZABALA, ARLENE (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This mixed method study aimed to assess the physical, chemical and microbiological properties of the Mamala River of Limay, Bataan. Twenty-two respondents were selected using criteria sampling technique. The physical properties of the river in terms of color, temperature, turbidity and odor, chemical properties like pH, Total Dissolved Solids (TDS), Total Suspended Solids (TSS), Biological Oxygen Demand (BOD) and sediments like lead, chromium and cadmium and microbiological property in terms of E.coli were evaluated. Unstructured interview was conducted to determine the past and present condition of the river. The water samples were taken from 3 water point locations (WPL) which revealed that all WPLs have standard color and temperature. However, WPL 1 has high turbidity and greasy oily odor while WPL 2 and 3 have normal turbidity and no odor. All WPLs have increasing ph and standard DO, BDO and sediment contents. The TDS level of WPL 1 is unacceptable while it exceeded the maximum TSS value. WPLs 2 and 3 have TDS and TSS value which are within the standard limit and has no E.coli. Also, it has experienced dramatic physical change, decreased in aquatic fauna and increased in number of family settling around its banks. Activities that enhance socialization and religiosity between and among people were no longer conducted in the river.